Rancang Bangun Game Edukasi 2D Pada Materi Berhitung Kelas 2 di SDN 15 Rambutan - Novrizah, Muhammad Rafli; Saputra, Herlambang; Putra, Rian Rahmanda (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Mobile application-based games are learning media that can be used to sharpen the brain's thinking and logic and increase children's learning creativity, as well as functioning as a medium of entertainment. Educational games are games that contain educational content and the aim is to stimulate children's interest in learning by absorbing learning material while playing. Games have various characteristics, including Adventure, Action Racing, Arcade, Logic, Board Games, Simulation, and Education. There are several types of tools for playing games, including Arcade games, PC games, console games, handheld games, and mobile games. 2D animation is a type of animation that is visually flat and can be created manually or with the help of a computer. 2D animation can be used in children's learning to increase their comprehension and interest in learning. This research designs and builds a 2D educational game for learning arithmetic in class 2 of SD Negeri 15 Rambutan as an effort to help students' learning development. Development methods are used to organize and manage each stage of development of this educational game.